1997
DOI: 10.1364/josaa.14.000547
|View full text |Cite
|
Sign up to set email alerts
|

Resolution: a survey

Abstract: Past and present approaches to the concept of optical resolution are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(191 citation statements)
references
References 72 publications
(75 reference statements)
2
183
0
6
Order By: Relevance
“…It was found that, without the use of the monochromator, Young's fringes only reached to about 70 pm. For a discussion of the relationship between information transfer and resolution, see den Dekker & van den Bos (1997), Van Aert et al (2006) and Peng et al (2008), and for a discussion of the use of Young's fringes to measure information transfer, see Barthel & Thust (2008). …”
Section: Instrument Parameters and Performancementioning
confidence: 99%
“…It was found that, without the use of the monochromator, Young's fringes only reached to about 70 pm. For a discussion of the relationship between information transfer and resolution, see den Dekker & van den Bos (1997), Van Aert et al (2006) and Peng et al (2008), and for a discussion of the use of Young's fringes to measure information transfer, see Barthel & Thust (2008). …”
Section: Instrument Parameters and Performancementioning
confidence: 99%
“…The second section of the paper focuses on the analytical derivation and analysis of the Angular Resolution Limit (ARL) [21], which is the minimal separation between two closely located targets at which they can be resolved separately. Deriving the ARL of a radar system is a fundamental problem [23] and has previously been formulated in a clutter free environment [21]. This paper considers multipath channels.…”
Section: Introductionmentioning
confidence: 99%
“…Since resolution is not unambiguously defined, various interpretations have been proposed during the last two centuries, most of them originally introduced in the field of optics [19,20,21]. The natural analogy between acoustics and optics is explored in this section to derive the most popular resolution criteria using a well-defined technique such as acoustic beamforming.…”
Section: Resolution Criteriamentioning
confidence: 99%